Pricing Sovereign Debt in Resource-Rich Economies - McGregor, Thomas (IMF Working Papers; Working Paper, 2019)
How do oil price movements affect sovereign spreads in an oil-dependent economy? I develop a stochastic general equilibrium model of an economy exposed to co-moving oil price and output processes, with endogenous sovereign default risk. The model explains a large proportion of business cycle fluctuations in interest-rate spreads in oil-exporting emerging market economies, particularly the countercyclicallity of interest rate spreads and oil prices. Higher risk-aversion, more impatient governments, larger oil shares and a stronger correlation between domestic output and oil price shocks all lead to stronger co-movements between risk premiums and the oil price.